2021
DOI: 10.1016/j.jaip.2020.11.038
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Adult and Pediatric Allergy & Immunology Services in the UK National Health Service

Abstract: Background The COVID-19 pandemic imposed multiple restrictions on healthcare services. Objective To investigate the impact of the pandemic on Allergy & Immunology (A&I) services in the UK. Methods National survey of all A&I services registered with the Royal College of Physicians and/or British Society for Allergy and Clinical Immunology. The survey covered staffing, facilities, personal protective equipment, appointments & patient review, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Previously strict guidelines were loosened to allow extra-license usage of home self-administration in patients with a history of anaphylaxis which had a clear trigger unrelated to omalizumab or in shortening the pathway [ 3 ]. The effects of the pandemic and these guidelines in the real world were investigated by Krishna et al [ 17 ]. It was found that 86-92% of immunology services continued routine appointments including new referrals but most of these consultations were telehealth or virtual, as there was a significant reduction in face-to-face consultations amongst the 99 immunology and allergy services participating in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously strict guidelines were loosened to allow extra-license usage of home self-administration in patients with a history of anaphylaxis which had a clear trigger unrelated to omalizumab or in shortening the pathway [ 3 ]. The effects of the pandemic and these guidelines in the real world were investigated by Krishna et al [ 17 ]. It was found that 86-92% of immunology services continued routine appointments including new referrals but most of these consultations were telehealth or virtual, as there was a significant reduction in face-to-face consultations amongst the 99 immunology and allergy services participating in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of services changed immunoglobulin administration regimens and reduced sublingual and subcutaneous injection immunotherapy among other therapeutic procedures. Adverse outcomes relating to these changes primarily centred around the immunoglobulin replacement therapy, although some centres reported exacerbations of CSU relating to missed omalizumab doses [ 17 ]. One flaw of these reports is inconsistent coding of anaphylaxis and urticarial symptoms; it is possible that the incidents of urticaria may have been misdiagnosed as anaphylaxis, falsely raising the rate of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…Ozturk et al reported that only 21% of the respondents were continuing subcutaneous immunotherapy as usual during the COVID-19 pandemic [18]. Krishna et al reported that there was a highly significant decrease in subcutaneous immunotherapy up dosing and maintenance during the pandemic [19]. We predicted that many parents would temporarily suspend the home-based OIT for children with FA to avoid the risk of emergency visits and ambulatory care for adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Primary Investigators Akagawa Shohei MD, PhD 1 , Anzai Kaori, MD 2 , Bandou Kenji, MD 3 , Ikeda Akiko, MD 4 , Doi Masaaki, MD, PhD 5 , Enomoto Masahiro, MD, PhD 6 , Fujikawa Shiori, MD 7 , Nagai Megumi MD, PhD 8 , Nishiyama Atsuko, MD 9 , Otsuka Keita, MD 10 , Shimizu Satoko, MD 11,12 , Sugimoto Yukiko, MD 13 , Sumimoto Shinichi, MD, PhD 2 , Tanaka Yukiko, MD 14 , Tanaka Yuko, MD 15 , Tanaka Yuya, MD 16 , Wakahara Ryohei, MD, PhD 17 , Yamasaki Koji, MD, PhD 18 Co-Investigators Arima Tomoyuki, MD 8 , Imaide Aya, MD 6 , Fukasawa Yohei, MD 21 , Hashimoto Naoki, MD 19 , Masumi Hiroki MD 8 , Matsutani Eri, MD 3 , Kim Jong Soo, MD 20 , Nakai Yoko, MD 1 , Nakamichi Erina, MD 2 , Natsuki Momo MD 16 , Onaka Masayuki, MD 9 , Shingaki Tomoya, MD 20 , Sunaga Ayana, MD 3 , Tsurinaga Yuki, MD 21 , Yamada Saki, MD 20 , Yamagishi Mitsuru, MD 1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation